Hubungan Pengetahuan Dan Konsumsi Sugar Sweetened Beverages (Ssbs) Dengan Status Gizi Remaja Di Smpn 3 Surakarta - Nurmala, Dona, Tri Wibowo Anang S.B., S.KM, M.Gizi (2018)
Background : Adolescence is a period of rapid physical growth. Changes in physical growth that occur will affect health status and nutrition. Imbalances between the intake of needs will cause nutritional problems. Good knowledge of SSBs is the main thing in determining daily eating and drinking habits. Consumption of SSBs is a simple added sugar drink that can increase the energy content, but has little other nutrients. SSBs in Indonesia contains 37-54 g of sugar in a serving package of 300-500 mL. The amount of sugar content exceeds. Excess consumption of sweetened beverages can be a cause of obesity. Objective: To determine the association of knowledge and consumption sugar swetened beverages (ssbs) to nutrition status of adolescent at junior high school negeri 3 Surakarta. Methods: This research is an observational with cross-sectional approach. The number of research subjects as many as 62 selected by the method proportional random sampling. Knowledge Data from a questionnaire containing 20 questions. Data Consumption SSBs from Semi Quantitative Food Frequency Questionnaire (SQ-FFQ) last 1 month. Data analysis with Pearson Product Moment. Results : Mostly of the subjects had normal nutritional status of 62.9%. Mostly of the study subjects had a good knowledge of sugar sweetened beverages 56.5%. Mostly of the subjects studied the consumption of SSBs in more category 79%. Result of Pearson Product Moment for knowledge with nutritional status p value = 0.4, and consumption of SSBs with nutritional status p value = 0.5. Conclusion: There was no association of knowledge to nutritional status and consumption sugar sweetened beverages to nutritional status